The Role of Personal Branding in Mediating the Influence of Credibility on Taxpayer Compliance at KPP Pratama Medan Timur - Gultom, Benjamin; B, Mesra; Isa Indrawan, Muhammad (International Conference Epicentrum of Economic Global Framework, 2025)
This study aims to analyze the effect of credibility on taxpayer compliance, with personal branding as an intervening variable, at the Medan Timur Tax Office. This study employs a quantitative approach using a survey method. The sample consisted of 100 individual taxpayers selected using purposive sampling. Data collection was conducted via a questionnaire using a Likert scale and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0. The results indicate that credibility has a positive and significant effect on taxpayer compliance. Credibility also has a positive and significant effect on personal branding. Furthermore, personal branding has a positive and significant effect on taxpayer compliance. The results of the indirect effect test indicate that personal branding significantly mediates the effect of credibility on taxpayer compliance. The coefficient of determination indicates that credibility explains 11.9 percent of the variance in personal branding, while taxpayer compliance is explained by credibility and personal branding to the extent of 44.2 percent. These findings suggest that enhancing the credibility of tax officials through strengthened personal branding can promote increased taxpayer compliance at the Medan Timur Primary Tax Office.